The effectiveness of catharsis-education-action (CEA) counseling versus the standard clinic advice for the management of type 2 diabetes mellitus at out-patient family medicine clinic a randomized controlled trial - Limoso, David Dexter V.
Background: The burden of suffering of diabetes is immense. The Family Medicine clinic averages more than 200 cases of diabetes per month, about 6.7% of the total cases seen, and ranking consistently in the top ten morbidities. Many studies have concluded that counseling is effective as an intervention in better management of patients with diabetes resulting to improved quality of life. The Catharsis-Education-Action (CEA) counseling is a 15-30 minute method of counseling that uses the biopsychosocial approach, addressing not just the physical illness but also the emotional impact of that illness. The counseling intervention consists of the following steps: (1) Catharsis elicits emotions and perceptions of patient about his illness and identifies the emotionally critical misperceptions (ECMs); (2) Education corrects the misperceptions; (3) Action consists of recommendations and prescriptions offered by the doctor.This study investigates the effectiveness of CEA counseling specific for the management of diabetes in improving the quality of life of patients.